Exergy, Economic and Environmental Analysis of a Direct Absorption Parabolic Trough Collector Filled with Porous Metal Foam - Murtadha Zahi Khattar; Mohammad Mahdi Heyhat (Energies, 2022)
A direct absorption parabolic trough solar collector (DAPTC) integrated with porous foam as a volumetric absorber has the potential to be applied as an energy conversion integrant of future renewable energy systems. The present study comprehensively analyzes a DAPTC in terms of exergy, economic, and environmental analysis for different porous configuration inserts in the absorber tube. Ten different arrangements of porous foam are examined at several HTF flow rates (40–120 L/h) and inlet temperatures (20–40 °C). The exergy efficiency, entropy generation, Bejan number, and pumping power are investigated for all cases. Obtained results indicate that fully filling the absorber tube with porous foam leads to a maximum exergy efficiency of 20.4% at the lowest inlet temperature (20 °C) and highest flow rate (120 L/h). However, the Bejan number reaches its minimum value due to the highest pumping power in this case. Consequently, all mentioned performance parameters should be considered simultaneously. Finally, the environmental and economic analyses are conducted. The results show that fully filling the absorber tube with porous foam reflects the best heat production cost, which can reduced the embodied energy, embodied water, and CO2 emission by 559.5 MJ, 1520.8 kL, and 339.62 kg, respectively, compared to the base case at the flow rate of 120 L/h.